Control method and detection method for orientation arrangement of multilayer graphene in magnetic composite material system
By using the anisotropic antimagnetic properties of multi-layer graphene in magnetic composite materials and applying a magnetic field for orientation arrangement, the problems of poor thermal conductivity and low tensile coefficient of traditional magnetic materials are solved, and the preparation of high-performance magnetic composite materials is realized.
Patent Information
- Application Number
- CN202411622693.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-04-15
AI Technical Summary
Traditional sintered magnetic materials have problems such as poor thermal conductivity, severe heat accumulation, excessive size and low tensile coefficient, which are difficult to meet the needs of high frequency, miniaturization and flexibility in clean energy, micro-motors and medical instruments.
By mixing multilayer graphene, magnetic powder and epoxy resin binder, using the anisotropic antimagnetic properties of multilayer graphene, applying a single-direction magnetic field for curing, the sheet or vertical orientation arrangement of multilayer graphene in magnetic composite material is achieved.
It realizes anisotropy of physical properties such as magnetic, thermal conductivity, and mechanics, and creates high-performance magnetic composite materials, meeting the needs of high frequency, miniaturization and flexibility.
Smart Images

Figure CN119833302A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of magnetic composite material systems, and in particular to a control method and a detection method for the orientation arrangement of multilayer graphene in a magnetic composite material system, and an application of the control method. Background Art
[0002] Magnetic materials are widely used in modern industry, such as trams, telephones, CNC machine tools, magnetic instruments and medical magnetic wires, etc., and are called "industrial vitamins". With the development of clean energy, micro motors and medical instruments, new requirements for the application of magnetic materials are high frequency, miniaturization and flexibility. Traditional sintered magnetic materials have problems such as poor thermal conductivity, serious heat accumulation, oversize and low tensile strength, which makes bonded magnetic composite materials receive more attention. Graphene has excellent thermal conductivity in the ab plane at room temperature (1000W·m -1 ·k -1 The thickness in the c direction is only nm, the density is small, and the specific surface area is large (1000m 2 / g level), stable chemical properties, and is a good composite material additive. Mixing multilayer graphene, magnetic powder and binder can prepare a magnetic composite material with good heat dissipation performance, mechanical properties and chemical stability.
[0003] The physical properties of multilayer graphene are anisotropic, and it needs to be arranged in a specific way at the microscopic level to obtain good macroscopic properties. The properties are also related to the degree of orientation of the arrangement. Multilayer graphene or graphene can be oriented in a magnetic field by utilizing its anisotropic anti-magnetism, but the traditional magnetic field orientation method can only orient multilayer graphene in a single direction: for example, when multilayer graphene is oriented by calendering, the material needs to be deformed. When the magnetic material matrix does not have shape anisotropy, this method is not suitable for the preparation of magnetic composite materials. Summary of the invention
[0004] The purpose of the present invention is to provide a control method and detection method for the orientation arrangement of multilayer graphene in a magnetic composite material system, and an application of the control method. The control method utilizes the anisotropic anti-magnetism of multilayer graphene, and through two different external magnetic field methods, the multilayer graphene is oriented in layers or vertically in the magnetic composite material to achieve anisotropy of physical properties such as magnetic, thermal conductivity, and mechanics, thereby creating a high-performance magnetic composite material.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for controlling the orientation of multilayer graphene in a magnetic composite material system, comprising the following steps:
[0007] The multilayer graphene, magnetic powder and epoxy resin binder are mixed to obtain a composite slurry;
[0008] The composite slurry is placed in a mold and flattened, and a magnetic field in a single direction is applied to solidify the composite slurry to obtain a magnetic composite material containing oriented multi-layer graphene;
[0009] The interior of the mold is cylindrical.
[0010] Preferably, when the direction of the magnetic field is parallel to the circular surface of the mold cylinder and rotates along the axial direction of the cylinder, the ab plane of the multilayer graphene is parallel to the circular surface of the mold cylinder, which is referred to as sheet orientation;
[0011] When the direction of the magnetic field is parallel to the axial direction of the mold cylinder, the ab plane of the multilayer graphene is perpendicular to the circular plane of the mold cylinder, which is referred to as vertical orientation.
[0012] Preferably, the number of layers of the multilayer graphene is 10 to 50, and the size of the ab plane is 1 to 10 μm;
[0013] The particle size of the magnetic powder is 1 to 25 μm.
[0014] Preferably, the mass ratio of the multilayer graphene to the epoxy resin binder is 1:(25-200);
[0015] The mass ratio of the magnetic powder to the epoxy resin binder is 1:(0.5-5).
[0016] Preferably, the particle size of the magnetic powder is 1 to 25 μm.
[0017] Preferably, the magnitude of the magnetic field is 0.3-1.0T.
[0018] Preferably, the curing includes a first curing and a second curing performed sequentially;
[0019] The first curing is performed under the condition of applying a magnetic field, and the first curing time is 1 to 2 hours;
[0020] The second curing is performed without applying a magnetic field, and the time of the second curing is 3 to 12 hours.
[0021] The present invention also provides a method for detecting the orientation of a magnetic composite material containing multi-layer graphene and oriented multi-layer graphene, comprising the following steps:
[0022] Performing an X-ray diffraction test on the magnetic composite material containing oriented multilayer graphene, and after deducting the diffraction peak of the magnetic powder, judging the orientation of the multilayer graphene in the magnetic composite material system by judging the ratio of the peak value of the multilayer graphene characteristic peak in the magnetic composite material to the peak value of the epoxy resin characteristic peak;
[0023] The X-ray diffraction test is a 2θ mode diffraction test;
[0024] The magnetic composite material containing oriented multilayer graphene is a magnetic composite material containing oriented multilayer graphene prepared by the control method described in the above technical solution;
[0025] During the X-ray diffraction test, the upper circular surface of the magnetic composite material containing oriented multilayer graphene coincides with the X-ray test plane;
[0026] The ratio of the diffraction peak intensity value of the multilayer graphene (002) in the magnetic composite material containing the oriented multilayer graphene to the characteristic peak intensity value of the epoxy resin after curing is K, and K=tan(θ). When θ=0-45°, the multilayer graphene in the magnetic composite material containing the oriented multilayer graphene is mainly arranged in a vertical orientation, and the degree of vertical orientation of the multilayer graphene in the magnetic composite material containing the oriented multilayer graphene increases with the decrease of the value of θ.
[0027] When θ=45-90°, the multilayer graphene in the magnetic composite material containing oriented multilayer graphene is mainly arranged in a sheet orientation, and the orientation degree of the sheet orientation of the multilayer graphene in the magnetic composite material containing oriented multilayer graphene increases with the increase of the value of θ.
[0028] Preferably, before performing the X-ray diffraction test, the upper circular surface of the magnetic composite material containing oriented multilayer graphene is polished;
[0029] The polishing is performed using sandpaper with 2000 mesh or above.
[0030] Preferably, the 2θ of the X-ray diffraction test is 20-60°, and after deducting the diffraction peak of the magnetic powder, the main peak count is >2000, and the signal-to-noise ratio is ≥10:1.
[0031] The present invention provides a method for controlling the oriented arrangement of multilayer graphene in a magnetic composite material system, comprising the following steps: mixing multilayer graphene, magnetic powder and epoxy resin binder to obtain composite slurry; placing the composite slurry in a mold and flattening it, applying a magnetic field in a single direction, and curing it to obtain a magnetic composite material containing oriented multilayer graphene; the interior of the mold is cylindrical.
[0032] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0033] The present invention adds multilayer graphene to an epoxy resin binder to prepare a composite slurry, which is simple to operate and widely applicable to magnetic composite materials. The present invention uses the anisotropic anti-magnetism of multilayer graphene for orientation, and magnetic field orientation is also effective for magnetic materials. Therefore, this method can be extended to the joint orientation of magnetic materials and graphene in a binder to achieve anisotropy of physical properties such as magnetism, thermal conductivity, and mechanics, and create high-performance magnetic composite materials;
[0034] The above-mentioned method of applying a magnetic field realizes the flake-oriented arrangement and vertical-oriented arrangement of multilayer graphene in the magnetic composite material, respectively, enriching the means of regulating the orientation arrangement.
[0035] The present invention also provides a method for detecting the orientation arrangement of a magnetic composite material of multilayer graphene containing oriented multilayer graphene, comprising the following steps: performing an X-ray diffraction test on the magnetic composite material containing oriented multilayer graphene, and after deducting the diffraction peak of the magnetic powder, judging the orientation arrangement of the multilayer graphene in the magnetic composite material system by judging the ratio of the peak value of the characteristic peak of the multilayer graphene in the magnetic composite material to the peak value of the characteristic peak of the epoxy resin; the magnetic composite material containing oriented multilayer graphene is a magnetic composite material containing oriented multilayer graphene prepared by the control method described in the above technical scheme; during the X-ray diffraction test, the upper circular surface of the magnetic composite material containing oriented multilayer graphene coincides with the test plane of the X-ray. ; The ratio of the diffraction peak intensity value of multilayer graphene (002) in the magnetic composite material containing oriented multilayer graphene to the characteristic peak intensity value of epoxy resin after curing is K, assuming K=tan(θ), when θ=0-45°, the multilayer graphene in the magnetic composite material containing oriented multilayer graphene is mainly arranged in vertical orientation, and the degree of vertical orientation of the multilayer graphene in the magnetic composite material containing oriented multilayer graphene increases with the decrease of θ value; when θ=45-90°, the multilayer graphene in the magnetic composite material containing oriented multilayer graphene is mainly arranged in sheet orientation, and the degree of orientation of the sheet orientation of the multilayer graphene in the magnetic composite material containing oriented multilayer graphene increases with the increase of θ value. The detection method of the present invention can realize the rapid detection and judgment of the orientation result. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The following are the geometric diagrams of the placement of the flat sheet-like cylinder in the magnetic field and the X-ray test in Example 1 (a) and the X-ray test result diagram of the prepared composite material system containing multi-layer graphene with oriented arrangement (b);
[0037] Figure 2 Schematic diagram of the placement of the flat sheet-like cylinders in the vertically oriented arrangement in the magnetic field and the X-ray test geometry in Example 2 (a) and the X-ray test result diagram of the prepared composite material system containing multilayer graphene with oriented arrangement (b). DETAILED DESCRIPTION
[0038] The present invention provides a method for controlling the orientation of multilayer graphene in a magnetic composite material system, comprising the following steps:
[0039] The multilayer graphene, magnetic powder and epoxy resin binder are mixed to obtain a composite slurry;
[0040] The composite slurry is placed in a mold and flattened, and a magnetic field in a single direction is applied to solidify the composite slurry to obtain a magnetic composite material containing oriented multi-layer graphene;
[0041] The interior of the mold is cylindrical.
[0042] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0043] The present invention mixes multilayer graphene, magnetic powder and epoxy resin binder to obtain composite slurry.
[0044] In the present invention, the number of layers of the multilayer graphene is preferably 10 to 50, more preferably 10 to 30, and most preferably 15 to 25. The size of the ab plane in the multilayer graphene is preferably 1 to 10 μm, more preferably 3 to 7 μm, and most preferably 4 to 5 μm; the size of the magnetic powder particles is preferably 1 to 25 μm, more preferably 3-15 μm, and most preferably 5-10 μm. In the present invention, the ab plane in the multilayer graphene refers to the crystallographic ab plane of the multilayer graphite crystal.
[0045] In the present invention, the magnetic powder is preferably a permanent magnetic powder or a soft magnetic powder; the present invention has no special restrictions on the type of the permanent magnetic powder or the soft magnetic powder, and any type familiar to those skilled in the art can be used. In an embodiment of the present invention, the magnetic powder can be Sm2Fe 17 N3 permanent magnet powder or Y2Fe 17 Si soft magnetic powder.
[0046] In the present invention, the viscosity of the epoxy resin adhesive at room temperature is preferably 1000-6000 cps; the shortest curing time of the epoxy resin adhesive is ≥30 min. In the present invention, the epoxy resin adhesive preferably includes commercial epoxy resin and commercial epoxy resin curing agent; the mass ratio of the commercial epoxy resin and the commercial epoxy resin curing agent is preferably 2:1.
[0047] In the present invention, the mass ratio of the multilayer graphene to the epoxy resin binder is preferably 1: (25-200), more preferably 1: (50-160), and most preferably 1: (80-120). In the present invention, the mass ratio of the magnetic powder to the epoxy resin binder is preferably 1: (0.5-5), more preferably 1: (0.7-3), and most preferably 1: (0.9-1.5).
[0048] In the present invention, the mixing method is preferably to stir with a stirring rod, and the stirring rod is preferably non-static. In an embodiment of the present invention, the stirring rod is specifically a conductive metal needle. The present invention does not have any special limitation on the stirring process, and the multilayer graphene can be evenly dispersed in the epoxy resin binder by a process well known to those skilled in the art.
[0049] In the present invention, the mixing time is preferably ≤ 10 min. In an embodiment of the present invention, the mixing time is specifically 10 min.
[0050] After obtaining the composite slurry, the present invention places the composite slurry in a mold and flattens it, applies a magnetic field in a single direction, and solidifies it to obtain a magnetic composite material containing oriented multilayer graphene, and the interior of the mold is cylindrical.
[0051] In the present invention, the material of the mold is preferably polytetrafluoroethylene. The diameter of the cylindrical surface is preferably 1 cm or 2 cm, and the depth is preferably 1 mm or 2 mm.
[0052] In the present invention, the flattening process is preferably to pour the composite slurry into a mold to fill the mold, and to flatten and fix the upper and lower circular surfaces with a flat cover plate.
[0053] In the present invention, the magnitude of the magnetic field is preferably 0.3 to 1.0 T, more preferably 0.5 to 1.0 T, and most preferably 0.8 to 1.0 T. In the present invention, the magnetic field is preferably a stable magnetic field in a single direction applied by an electromagnet.
[0054] In the present invention, when the direction of the magnetic field is parallel to the circular surface of the mold cylinder and the cylinder rotates in the axial direction (the rotation rate is preferably 10 rpm), the orientation arrangement is that the ab plane of the multilayer graphene is parallel to the circular surface of the mold cylinder, which is referred to as lamellar orientation; when the direction of the magnetic field is parallel to the axial direction of the mold cylinder, the orientation arrangement is that the ab plane of the multilayer graphene is perpendicular to the circular surface of the mold cylinder, which is referred to as vertical orientation.
[0055] In the present invention, the above two magnetic field control methods respectively realize the oriented arrangement of multilayer graphene sheets in the magnetic composite material (such as Figure 1) and vertically oriented (as shown Figure 2 The two orientation modes (as shown) enrich the means of regulating orientation arrangement.
[0056] In the present invention, after the composite slurry is placed in a mold and pressed flat, the time for applying a magnetic field in a single direction is preferably ≤10 minutes, and most preferably ≤5 minutes. In an embodiment of the present invention, after the composite slurry is placed in a mold and pressed flat, the time for applying a magnetic field in a single direction is specifically 5 minutes or 10 minutes.
[0057] In the present invention, the curing preferably includes a first curing and a second curing performed sequentially; the first curing is preferably performed under the condition of applying a magnetic field, and the time of the first curing is preferably 1 to 2 hours; the second curing is preferably performed under the condition of not applying a magnetic field, and the time of the second curing is preferably 3 to 12 hours, more preferably 4 to 6 hours. The temperature of the second curing is preferably room temperature.
[0058] The present invention also provides a method for detecting the orientation arrangement of multilayer graphene in a magnetic composite material, comprising the following steps:
[0059] Performing an X-ray diffraction test on the magnetic composite material containing oriented multilayer graphene, and after deducting the diffraction peak of the magnetic powder, judging the orientation of the multilayer graphene in the magnetic composite material system by judging the ratio of the peak value of the multilayer graphene characteristic peak in the magnetic composite material to the peak value of the epoxy resin characteristic peak;
[0060] The magnetic composite material containing oriented multilayer graphene is a magnetic composite material containing oriented multilayer graphene prepared by the control method described in the above technical solution;
[0061] During the X-ray diffraction test, the upper circular surface of the magnetic composite material containing oriented multilayer graphene coincides with the X-ray test plane;
[0062] The ratio of the diffraction peak intensity value of the multilayer graphene (002) in the magnetic composite material containing the oriented multilayer graphene to the characteristic peak intensity value of the epoxy resin after curing is K, and K=tan(θ). When θ=0-45°, the multilayer graphene in the magnetic composite material containing the oriented multilayer graphene is mainly arranged in a vertical orientation, and the degree of vertical orientation of the multilayer graphene in the magnetic composite material containing the oriented multilayer graphene increases with the decrease of the value of θ.
[0063] When θ=45-90°, the multilayer graphene in the magnetic composite material containing oriented multilayer graphene is mainly arranged in a sheet orientation, and the orientation degree of the sheet orientation of the multilayer graphene in the magnetic composite material containing oriented multilayer graphene increases with the increase of the value of θ.
[0064] In the present invention, the X-ray diffraction test is preferably a 2θ mode diffraction test; the test angle of the X-ray diffraction test is preferably 20-60 degrees, and after deducting the diffraction peak of the magnetic powder, the main peak count is preferably >2000, and the signal-to-noise ratio is preferably ≥10:1.
[0065] The control method and detection method of the orientation arrangement of multilayer graphene in a magnetic composite material system provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0066] Example 1
[0067] 0.05 g of commercial multilayer graphene powder (10-20 layers, ab plane size 5-10 μm), 1.5 g of Sm2Fe 17 N3 permanent magnetic powder (particle size of 5-10 μm), 2 g of commercial epoxy resin (purchased from Shanghai Kangda New Materials) and 1 g of commercial epoxy resin curing agent (purchased from Shanghai Kangda New Materials) are placed in a container, and a conductive metal needle is used to stir so that the multilayer graphene powder is completely dispersed in the epoxy resin. The mixing is completed within 10 minutes to obtain a composite slurry;
[0068] The composite slurry is poured into a polytetrafluoroethylene mold with a straight cylindrical interior (the inner diameter of the mold is 2 cm and the height is 1 mm) until the polytetrafluoroethylene mold is filled, and the upper and lower circular surfaces are flattened and fixed with a flat cover plate, and placed in the area where the electromagnet provides a magnetic field (the whole process is completed within 5 minutes).
[0069] The sheet orientation arrangement method is adopted: the magnetic field direction is parallel to the circular surface of the mold cylinder, and the cylinder rotates along the axial direction (such as Figure 1 As shown), the magnetic field size is 0.5T, the cylinder rotates at a speed of 10rpm in the axial direction, and after curing for 1 hour while maintaining the magnetic field and the cylinder rotating, the magnetic field is removed, the rotation is stopped, and the curing is allowed to stand for 3 hours to obtain a composite material system containing multilayer graphene with oriented arrangement;
[0070] The composite material system was polished with 2000-grit sandpaper to remove the burrs on the surface, and then the cylindrical piece was placed on the test platform of the X-ray diffractometer, the circular surface was parallel to the test platform and was on the reference plane of the diffraction test, and the normal direction of the circular surface was parallel to the normal direction of the 2θ mode test light path (the placement of the flat cylindrical piece in the magnetic field in the lamellar orientation arrangement of the magnetic composite material and the geometric diagram of the X-ray test are shown in Figure 1 As shown in (a), the flake orientation control method can achieve the arrangement of multi-layer graphene ab plane parallel to the circular surface of the mold cylinder). The conditions of the X-ray diffraction test are: the test angle 2θ is 20-60 degrees, and the total test time is 20 minutes. After deducting the diffraction peak of the magnetic powder, the test results are as follows Figure 1 As shown in (b); according to Figure 1 From the test results in (b), the ratio K of the diffraction peak intensity value of multilayer graphene (002) to the 30° diffraction bun peak of epoxy resin after curing is calculated. Assume tan(θ)=K, and use θ to measure the angle between the c direction of multilayer graphene and the X-ray diffraction test reference plane. θ is between 0-90°. Among them, the ratio K of the diffraction peak intensity value of multilayer graphene (002) to the peak intensity of the 30° diffraction bun peak of epoxy resin after curing is 14.3. According to "tan(θ)=K", θ is 86°, which indicates that the c direction of multilayer graphene basically coincides with the normal direction of X-ray diffraction (also the normal of the cylindrical surface), and the ab surface of multilayer graphene is parallel to the circular surface, thus realizing the lamellar orientation control of multilayer graphene in magnetic composite materials.
[0071] Example 2
[0072] 0.025g of commercial multilayer graphene powder (10-20 layers, ab plane size 5-10μm), 1g of Y2Fe 17 Si soft magnetic powder, 1 g of commercial epoxy resin (purchased from Shanghai Kangda New Materials) and 0.5 g of commercial epoxy resin curing agent (purchased from Shanghai Kangda New Materials) were placed in a container, and a conductive metal needle was used to stir so that the multilayer graphene powder was completely dispersed in the epoxy resin. The mixing was completed within 10 minutes to obtain a composite slurry;
[0073] The composite slurry is poured into a polytetrafluoroethylene mold with a straight cylindrical interior (the inner diameter of the mold is 1.5 cm and the height is 1 mm) until the polytetrafluoroethylene mold is filled, and the upper and lower circular surfaces are flattened and fixed with a flat cover plate, and placed in the area where the electromagnet provides a magnetic field (the whole process is completed within 10 minutes).
[0074] A vertical orientation arrangement method is adopted: the direction of the magnetic field is perpendicular to the circular surface of the mold cylinder, the magnetic field size is 0.7T, the magnetic field is maintained for 2 hours of curing, the magnetic field is removed, and the curing is allowed to stand for 5 hours to obtain a magnetic composite material containing oriented multilayer graphene;
[0075] The magnetic composite material was polished with 3000-grit sandpaper to remove the burrs on the surface, and then the cylindrical piece was placed on the test platform of the X-ray diffractometer, the circular surface was parallel to the test platform and was on the reference plane of the diffraction test, and the normal direction of the circular surface was parallel to the normal direction of the 2θ mode test light path (the placement of the flat sheet-like cylinder in the vertical orientation arrangement of the magnetic composite material in the magnetic field and the X-ray test geometric diagram are shown in FIG. Figure 2 As shown in (a), the vertical orientation control method can achieve the arrangement of multi-layer graphene ab planes perpendicular to the circular surface of the mold cylinder). The conditions of the X-ray diffraction test are: the test angle 2θ is 20-60 degrees, and the total test time is 20 minutes. After deducting the diffraction peak of the magnetic powder, the test results are as follows Figure 2 As shown in (b); according to Figure 2 From the test results in (b), the ratio K of the diffraction peak intensity value of multilayer graphene (002) to the peak intensity of the 30° diffraction bun peak of the epoxy resin after curing is calculated. Assume tan(θ)=K, and use θ to measure the angle between the c direction of the multilayer graphene and the X-ray diffraction test reference plane. θ is between 0-90°. Among them, the ratio K of the diffraction peak intensity value of the multilayer graphene (002) to the 30° diffraction bun peak of the epoxy resin after curing is 0.466. According to "tan(θ)=K", θ is 25°, which indicates that the c direction of the multilayer graphene is mostly perpendicular to the normal direction of the X-ray diffraction (also the normal of the cylindrical surface), and the ab plane of the multilayer graphene is mostly perpendicular to the circular surface, thus realizing the vertical orientation control of the multilayer graphene in the magnetic composite material.
[0076] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for controlling the orientation of multilayer graphene in a magnetic composite material system, characterized in that: The following steps are involved: The multilayer graphene, magnetic powder and epoxy resin binder are mixed to obtain a composite slurry; The composite slurry is placed in a mold and flattened, and a magnetic field in a single direction is applied to solidify the composite slurry to obtain a magnetic composite material containing oriented multi-layer graphene; The interior of the mold is cylindrical.
2. The control method according to claim 1, characterized in that: When the direction of the magnetic field is parallel to the circular surface of the mold cylinder and rotates along the axial direction of the cylinder, the ab plane of the multilayer graphene is parallel to the circular surface of the mold cylinder, which is referred to as sheet orientation; When the direction of the magnetic field is parallel to the axial direction of the mold cylinder, the ab plane of the multilayer graphene is perpendicular to the circular plane of the mold cylinder, which is referred to as vertical orientation.
3. The control method according to claim 1, characterized in that: The number of layers of the multilayer graphene is 10 to 50, and the size of the ab plane is 1 to 10 μm; The particle size of the magnetic powder is 1 to 25 μm.
4. The control method according to claim 1, characterized in that: The mass ratio of the multilayer graphene to the epoxy resin binder is 1:(25-200); The mass ratio of the magnetic powder to the epoxy resin binder is 1:(0.5-5).
5. The control method according to claim 1, 3 or 4, characterized in that: The particle size of the magnetic powder is 1 to 25 μm.
6. The control method according to claim 1 or 2, characterized in that: The magnitude of the magnetic field is 0.3-1.0T.
7. The control method according to claim 1, characterized in that: The curing includes a first curing and a second curing performed sequentially; The first curing is performed under the condition of applying a magnetic field, and the first curing time is 1 to 2 hours; The second curing is performed without applying a magnetic field, and the second curing time is 3 to 12 hours.
8. A method for detecting the alignment of a magnetic composite material containing multilayer graphene and oriented multilayer graphene, characterized in that: The following steps are involved: Performing an X-ray diffraction test on the magnetic composite material containing oriented multilayer graphene, and after deducting the diffraction peak of the magnetic powder, judging the orientation of the multilayer graphene in the magnetic composite material system by judging the ratio of the peak value of the multilayer graphene characteristic peak in the magnetic composite material to the peak value of the epoxy resin characteristic peak; The magnetic composite material containing oriented multilayer graphene is a magnetic composite material containing oriented multilayer graphene prepared by the control method according to any one of claims 1 to 7; During the X-ray diffraction test, the upper circular surface of the magnetic composite material containing oriented multilayer graphene coincides with the X-ray test plane; The ratio of the diffraction peak intensity value of the multilayer graphene (002) in the magnetic composite material containing the oriented multilayer graphene to the characteristic peak intensity value of the epoxy resin after curing is K, and K=tan(θ). When θ=0-45°, the multilayer graphene in the magnetic composite material containing the oriented multilayer graphene is mainly arranged in a vertical orientation, and the degree of vertical orientation of the multilayer graphene in the magnetic composite material containing the oriented multilayer graphene increases with the decrease of the value of θ. When θ=45-90°, the multilayer graphene in the magnetic composite material containing oriented multilayer graphene is mainly arranged in a sheet orientation, and the orientation degree of the sheet orientation of the multilayer graphene in the magnetic composite material containing oriented multilayer graphene increases with the increase of the value of θ.
9. The detection method according to claim 8, characterized in that: Before performing the X-ray diffraction test, the upper circular surface of the magnetic composite material containing oriented multilayer graphene is polished; The polishing is performed using sandpaper with 2000 mesh or above.
10. The detection method according to claim 8, characterized in that: The 2θ of the X-ray diffraction test is 20-60°, and after deducting the diffraction peak of the magnetic powder, the main peak count is >2000, and the signal-to-noise ratio is ≥10:1.